Liberalismo Perfeccionista y Liberalismo Político. (Parte II) - Nussbaum, Martha C. (Pontificia Universidad Católica del Perú, 2017)
In the first part of the article, the author discusses two types of liberalism from the thoughts of prominent philosophers. On the one hand, she analyzes the ideas of Isaiah Berlin and Joseph Raz as examples of perfectionist liberalism and, on the other hand, those of John Rawls and Charles Larmore as examples of political liberalism. He then discusses the notion of comprehensive doctrines in John Rawls’s oeuvre, for from Nussbaum´s perspective, the construction of this notion brings Rawls close to a variant of perfectionist liberalism that he himself would try to avoid. That is why Nussbaum’s proposal is to restore a notion of comprehensive doctrines simply understood as those kinds of doctrines to which reasonable citizens adhere.

En la primera parte del artículo la autora discute dos variantes de liberalismo a partir del pensamiento de destacados filósofos. Por un lado, analiza las ideas de Isaiah Berlin y Joseph Raz como ejemplos de liberalismo perfeccionista y, por el otro, las de John Rawls y Charles Larmore como ejemplos de liberalismo político. A continuación problematiza la noción de doctrinas comprehensivas en la obra de John Rawls, pues desde la perspectiva de Nussbaum, la construcción de dicha noción acerca a Rawls a una variante de liberalismo perfeccionista que él mismo trataría de evitar. Es por ello que la propuesta de Nussbaum consiste en restaurar una noción de doctrinas comprehensivas simplemente como aquel tipo de doctrinas a las que adhieren ciudadanos razonables.
Perfectionist Liberalism and Political Liberalism. (Part II)
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.00